Cost-Effectiveness Analysis of Pembrolizumab Plus Chemotherapy vs. Chemotherapy Alone as First-Line Treatment in Patients With Esophageal Squamous Cell Carcinoma and PD-L1 CPS of 10 or More - Zhiwei Zheng; Jingrong Lin; Huide Zhu; Hongfu Cai (Frontiers Media S.A., 2022)
BackgroundThis study aimed to analyze the economics of pembrolizumab plus chemotherapy as first-line treatment in patients with esophageal squamous cell carcinoma (ESCC) and programmed cell death-Ligand 1 (PD-L1) combined positive score (CPS) of 10 or more in China.MethodsBased on the advanced ESCC of the KEYNOTE-590 clinical trial data, a Markov model was performed to simulate the clinical course and evaluate the patient's total lifetime, total costs, quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratio (ICER) for pembrolizumab plus chemotherapy (cisplatin and 5-fluorouracil) vs. chemotherapy alone in first-line treatment of ESCC and PD-L1 CPS of 10 or more. Utility values and direct costs related to the treatments were gathered from the published literature data. One-way and probabilistic sensitivity analyses were conducted to check the stability of the model.ResultsThe baseline analysis indicated that the incremental effectiveness and cost of pembrolizumab plus chemotherapy vs. chemotherapy alone added 1.23 QALYs and resulted in an incremental cost of $51,320.22, which had an ICER of $41,805.12/QALY, higher than the willingness-to-pay (WTP) threshold of China ($37,663.26/QALY). The sensitivity analysis demonstrated that the ICERs were most sensitive to the cycle of pembrolizumab used and the cost of pembrolizumab.ConclusionThe result of our present analysis suggests that the addition of pembrolizumab plus chemotherapy as first-line treatment might not be cost-effective for patients with ESCC and PD-L1 CPS of 10 or more in China.